Video mapping as a didactic strategy to design learning situations in teacher training (ASRI. Art and Society. Journal for Research in Arts and Digital Humanities, 2025)
Video mapping is a technique widely used in public art that transforms the appearance of all kinds of surfaces with projections.Given that the means used to perform these productions are the same that we can find in a classroom, this article proposes a teaching strategy based on the use of these ICTs to achieve artistic and technological literacy among trainee teachers.As a result, three artistic interventions developed in three different contexts and based on the methodological foundation of a/r/tography are presented.
Keywords: A/r/tography; collaborative learning; ICT; learning situations; teacher training